PERAN KEPALA SEKOLAH DALAM PENINGKATAN PROFESIONALISME GURU DI SEKOLAH MENENGAH PERTAMA NEGERI 1 MRANGGEN KABUPATEN DEMAK - Nur Afifah Nur; Yovitha Yuliejantiningsih; Titik Haryati (STKIP Subang, 2023)
Teachers play an important role in the world of education. Improving the quality of education is determined by efforts to improve teacher professionalism. Therefore, the role of the principal is needed in improving teacher professionalism. The purpose of this study is to describe and analyze the role of the principal as a manager in improving teacher professionalism at SMP Negeri 1 Mranggen and to describe and analyze the role of the principal as a supervisor in improving teacher professionalism at SMP Negeri 1 Mranggen. The research approach used is a qualitative approach. This type of research is a case study. The data collection techniques used are interviews, observation and documentation. The results showed that: (1) The principal has prepared a RKAS in which there is a plan to increase teacher competence, competency-based education and training programs, and planning PKB activities. All teachers at SMP Negeri 1 Mranggen have met the educational qualification standard, namely S1, even 15 teachers have S2 certificates. (2) The headmaster together with the curriculum team have prepared a teacher academic supervision program in accordance with the procedure. However, the implementation of teacher supervision at SMP Negeri 1 Mranggen is only carried out once a year, not per semester.